2003
DOI: 10.1061/(asce)0887-3828(2003)17:3(151)
|View full text |Cite
|
Sign up to set email alerts
|

Study of Recent Building Failures in the United States

Abstract: A total of 225 building failures in the United States from 1989 to 2000 were recorded in this study. The result shows that failures of low-rise buildings constitute about 63% of all cases, followed by multistory buildings as a distant second. In terms of their functions, apartments are the most frequent to fail. External events and construction and maintenance deficiencies have been identified as the most frequent principal causes. External events include rain, wind, snow, vehicular impact, and collision. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 5 publications
3
35
0
3
Order By: Relevance
“…Being a result of common conditions such as accidental impact, construction defects, structural overloads and failure of foundations, it is the cause of most structural collapse around the world (Wardhana and Hadipriono, 2003). The United States General Service Administration (GSA) and the Department of Defence (DoD) have presented practical guidelines (GSA, 2003 andDoD, 2005) for progressive collapse analysis of building.…”
Section: Introductionmentioning
confidence: 99%
“…Being a result of common conditions such as accidental impact, construction defects, structural overloads and failure of foundations, it is the cause of most structural collapse around the world (Wardhana and Hadipriono, 2003). The United States General Service Administration (GSA) and the Department of Defence (DoD) have presented practical guidelines (GSA, 2003 andDoD, 2005) for progressive collapse analysis of building.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Wardhana and Hadipriono [8] recently published statistical data on total number of highway bridges and number of collapsed bridges in the US over a period of 11 years (1989-2000). Wardhana and Hadipriono [8] reported that there are 691,060 highway bridges.…”
Section: Probabilistic Risk Of Fire In Bridgesmentioning
confidence: 97%
“…However, in current practice, structural members in bridges are to be designed for earthquake loading but not for fire hazard [7]. In addition, Wardhaua and Hadipriono [8] as well as Scheer [9] showed that 3.2% and 4.9% of total bridge population experienced some level of collapse due to fire, respectively. Similarly, Kodur et al [1,10] reviewed recent bridge fire incidents and concluded that bridge fires can lead to major structural damage or collapse of bridges.…”
Section: Introductionmentioning
confidence: 99%
“…The common causes of the defects highlighted are: (1) lack of monitoring or supervision by responsible authorities, (2) lack of technical expertise and full reliance on contractors or consultants, (3) lack of coordination between agencies involved, (4) internal problems faced by the contractors, and (5) contractual issues. Notwithstanding, the government have realised that this cannot continue and they are not getting the value for money for their projects c) recording and publishing several construction defects that occurred in public buildings and their lessonlearnt in a book d) enforcing Defects Liability Management System for the management of defective works on seven hospital projects constructed in the Malaysian Eight Plan (RMK8) Following this, [20] found that defects are being repeated in many projects even when constructed by the same contractor. Thus, a study on the nature of the defects and possible approaches to track their root cause is very necessary.…”
Section: Defects and Its Implication In The Malaysian Construction Inmentioning
confidence: 99%